STUDIES ON KERATINOLYTIC ACTIVITY OF ALKALINE PROTEASES FROM HALOPHILIC BACTERIA - V. K. NIGAM; P. SINGHAL; A. S. VIDYARTHI; M. K. MOHAN; P. GHOSH (International Journal of Pharma and Bio Sciences, 2013)
Alkaline proteases producing halophilic bacteria isolated from Sambar Lake, Rajasthan were investigated for keratinolytic activity. The aim of this study was to optimize culture conditions for maximum enzyme production as well as characterization of proteases with keratinolytic action. Casein was used as sole carbon and nitrogen source for alkaline protease production at 37°C and 150 rpm. Higher keratinolytic activity was obtained when the production medium was supplemented with chicken feathers at a concentration of 1g/L. Optimum pH and temperature for maximum activity was found to be 9.0 and 50°C respectively. The enzyme is stable at alkaline pH (8-9). It has high thermostability at 50°C and lost 25% of its keratinolytic activity after 8 h of incubation at 50°C.